EFFECT OF FERMENTATION OPTIMIZATION WITH PH CONTROL ON ACTINOMYCETES ISOLATE AS ANTIBACTERIAL STAPHYLOCOCCUS AUREUS - Joanne, Anastasia; Bahar, Meiskha; Muktamiroh, Hikmah; Setyaningsih, Yuni (Universitas Medan Area, 2024)
Actinomycetes are Gram-positive bacilli noted for their secondary metabolites that are effective as antibacterials. Production of the antibacterial compounds is determined by nutrition, temperature, pH, and fermentation time. This study aims to study the antibacterial activity of Actinomycetes isolates from Bogor Botanical Gardens soil by fermentation optimization with pH control on the 3rd, 4th, and 5th day against the growth of Staphylococcus aureus bacteria. Actinomycetes isolates were inoculated on Starch Casein Agar (SCA) and fermented in liquid media containing 7 g glucose, 14 g mannitol, 14 g peptone for 5 days with the pH controlled within the range of 6.2–6.8. Antibacterial test method against S.aureus using well diffusion method with Nutrient Agar (NA) media. The inhibition zone diameter was measured every 24 hours and and the results obtained were 3.73 mm; 6.05mm; and 5.34mm. Those data were analyzed using the Kruskal-Wallis test and then continued with the Mann Whitney test which had significant differences between groups. The conclusion of the study is Actinomycetes isolates have antibacterial potential against the growth of S. aureus with the largest average diameter of inhibition zone in the 4th day fermentation group, which had moderate inhibition.